2010
DOI: 10.5271/sjweh.3137
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and subsequent sleep problems – the Helsinki Health Study

Abstract: Lallukka T, Rahkonen O, Lahelma E. Workplace bullying and subsequent sleep problems -the Helsinki Health Study. Scand J Work Environ Health. 2011;37(3):204-212. doi:10.5271/sjweh.3137 Objective The associations between workplace bullying and subsequent sleep problems are poorly understood.This study aims to address this evidence gap. MethodsWe used the Helsinki Health Study questionnaire survey data at baseline in 2000-2002 and follow-up in 2007 (N=7332). The 4-item Jenkins sleep questionnaire was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 47 publications
4
49
0
1
Order By: Relevance
“…We took this additional information into consideration and, in case of agreement, the quality ratings were adjusted accordingly. The comments resulted in six minor changes of our initial quality rating (41)(42)(43)(44).…”
Section: Statistical Adjustmentmentioning
confidence: 99%
“…We took this additional information into consideration and, in case of agreement, the quality ratings were adjusted accordingly. The comments resulted in six minor changes of our initial quality rating (41)(42)(43)(44).…”
Section: Statistical Adjustmentmentioning
confidence: 99%
“…Psychological and psychosomatic reactions become more prominent and severe with persistent exposure. Illustrating these reactions, research shows that prolonged bullying is associated with subsequent reports of anxiety (8,15), depression (8,16), suicidal ideation (17,18), headache (19), and sleep problems (20)(21)(22). In a meta-analysis it was found that exposure to bullying predicted subsequent mental health complaints [odds ratio (OR) 1.68, 95% confidence interval (95% CI) 1.35-2.09] and somatic complaints (OR 1.77, 95% CI 1.41-2.22) after adjusting for baseline health status (9).…”
mentioning
confidence: 99%
“…In Lallukka et al's prospective study (3), excluding respondents with mental health problems and adjusting for sleep problems at baseline resulted in attenuation of the observed association between bullying and sleep problems. We had similar findings with adjustment of T1-sleep problems and excluding respondents with depression.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted for age, gender, BMI, alcohol (drinks per week) and smoking at baseline since previous studies have shown differences in sleep patterns among men and women, with age, BMI and with alcohol intake (19)(20)(21). We also adjusted for working time, as working at night might affect sleep, education beyond primary and high school (three groups: <3 years; 3-4 years; >4 years) as used before in a study of workplace bullying, and T1-sleep problems (1,3). We identified respondents with depression estimated in the PRISME cohort from Schedules for Clinical Assessment in Neuropsychiatry (SCAN) interviews (12).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation